Presymptomatic treatment of classic late-infantile neuronal ceroid lipofuscinosis with cerliponase alfa - Schaefers, J.; van der Giessen, L. J.; Klees, C.; Jacobs, E. H.; Sieverdink, S.; Dremmen, M. H. G.; Spoor, J. K. H.; van der Ploeg, A. T.; van den Hout, J. M. P.; Huidekoper, H. H. (Orphanet journal of rare diseases, 2021)
Background Neuronal ceroid lipofuscinosis type 2 (CLN2 disease) is a rare rapidly progressive neurodegenerative disorder, resulting in early death. Intracerebroventricular enzyme replacement therapy (ERT) with cerliponase alfa is now available and has shown to delay disease progression in symptomatic patients. It is yet unknown if cerliponase alfa can prevent disease onset in presymptomatic patients. Results We evaluated the effect of 2 years of intracerebroventricular ERT in two siblings with CLN2 disease, one symptomatic (age 47 months) and one presymptomatic (age 23 months) at treatment start, using the CLN2 Clinical Rating Scale (CLN2 CRS), Gross Motor Function Measure-66 (GMFM-66) for motor function, Bayley Scales of Infant and Toddler Development, 3rd Edition, Dutch (BSID-III-NL) for neurocognitive development, brain MRI, and visual evoked potentials (VEP), electroretinogram (ERG) and retinoscopy for visual function. On the CLN2 CRS patient 1 showed a decline from 3 to 2 in the combined motor and language score due to regression in language use (CLN2 CRS total score after 2 years of treatment: 8), whereas a decline of 2 or more points in the combined motor and language score would be expected without treatment. Patient 2 retained the maximum score of 3 in all 4 subdomains (CLN2 CRS total score after 2 years of treatment: 12). The GMFM-66 total score declined from 46 to 39 in patient 1 and showed an age-appropriate increase from 66 to 84 in patient 2. Cognitive-developmental age decreased from 24 to 11 months in patient 1, whereas an increase in cognitive-developmental age from 21 to 39 months was seen in patient 2. Cerebral and cerebellar atrophy observed on MRI in patient 1 at age 42 months (before treatment) was not observed in patient 2 at age 48 months (after 2 years of treatment). Conclusion We show that cerliponase alfa is able to delay the onset of symptoms when treatment is started in a presymptomatic stage of CLN2 disease. Our results advocate the start of treatment at an early age before symptom onset, but should be confirmed in a larger cohort study.